Management of refeeding syndrome in a severely wasted complex case pediatric patient in a limited facilities hospital: a case report - Arief Rahman; Riona Sari; Epriyan Saputra (Medical Faculty of Brawijaya University, Indonesia, 2025)
Backgrounds: Refeeding syndrome is a life-threatening metabolic complication that may occur during nutritional rehabilitation in patients with severe malnutrition. Diagnosing this condition is particularly challenging in resource-limited settings due to the lack of comprehensive laboratory facilities, although prompt recognition and treatment are essential to prevent serious outcomes. Case Presentation: We report an 11-month-old boy presenting with pallor, generalized weakness, severe wasting, a senile facial appearance, prominent ribs, abdominal distention, phimosis, pedal edema, and global developmental delay. Pulmonary auscultation revealed fine crackles bilaterally. Laboratory investigations demonstrated very severe anemia (hemoglobin 2.7 g/dL), leukocytosis, hypoalbuminemia, and the presence of Ascaris lumbricoides ova. Chest radiography suggested pulmonary tuberculosis. The patient was treated with packed red cell transfusions, broad-spectrum intravenous antibiotics, multivitamins, folic acid, and first-line anti-tuberculosis drugs. Nutritional support was initiated cautiously following stabilization, but on day five, the patient developed recurrent pedal edema, hypokalemia, hypernatremia, and a further decline in serum albumin. Based on the consensus criteria of the American Society for Parenteral and Enteral Nutrition (ASPEN), a diagnosis of refeeding syndrome was established. Electrolyte abnormalities were corrected, and nutritional support was restarted from the stabilization phase with close monitoring. Anthelmintic and iron therapy were administered during the rehabilitation phase. The patient showed gradual clinical improvement and was discharged on day 26. Conclusion: Early diagnosis of refeeding syndrome is feasible in resource-limited hospitals using the updated diagnostic criteria provided by ASPEN. Careful nutritional repletion, timely administration of thiamine and multivitamins, correction and monitoring of electrolytes, and vigilant clinical observation are essential for the effective management of pediatric refeeding syndrome.